Synthesis, electrochemical and spectroelectrochemical properties of highly soluble tetra substituted phthalocyanines with [4-(thiophen-3-yl)-phenoxy] - Erdogmus, Ali; Koca, Atif; Ugur, Ahmet Lutfi; Erden, Ibrahim (ELSEVIER SCIENCE SA, 2011)
Zinc, oxo-titanium, cobalt, and manganese phthalocyanine derivatives substituted with nonperipheral 3-(tetra[4-(thiophen-3-yl)-phenoxy] moieties have been synthesized and characterized by elemental analysis, IR, H-1 NMR spectroscopy, electronic spectroscopy, and mass spectra. The compounds have good solubility in various polar and nonpolar organic solvents and not aggregated (in the same solvents) within a wide concentration range. Electrochemical and spectroelectrochemical measurements exhibit that incorporation redox active metal centers, Co-II, (TiO)-O-IV and (MnOAc)-O-III into the phthalocyanine core extend the redox richness of the Pc ring with the reversible metal-based reduction and oxidation couples of the metal centers in addition to the common Pc ring-based electron transfer processes. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Oxotitanium; Cobalt; Manganese; Phthalocya nines; Electrochemistry; Spectroelectrochemistry; IN-SITU; MANGANESE PHTHALOCYANINE; METAL-FREE; MONONUCLEAR; COMPLEXES; Materials Science; Physics; Polymer Science